CORRELATION BETWEEN SMARTPHONE DEPENDENCY AND READING CULTURE IN STUDENTS OF ANAMBRA STATE POLYTECHNIC - Chukwuka Sunda, Nwajikwa (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2023)
Reading is a fundamental skill in any culture and an integral aspect of society's educational infrastructure. However, several obstacles face the reading culture in Nigeria, such as the ever-increasing advancements in mobile technology. The present study examined over-dependency on smartphones as a potential variable that could account for the variations in reading culture among students in Anambra State, Nigeria. Two hundred and fifty-two undergraduates enrolled in three public higher education institutions in Anambra State participated in the survey. The respondents completed a self-report measure of the Smartphone Addiction Scale-Short Version (SAS-SV) and Reading Culture Scale. The simple regression analysis performed on the data revealed that smartphone dependency statistically significantly correlated with the student's reading culture ? = .66. The findings suggest that the hypothesis that the prevalence of smartphone dependency would significantly predict reading culture among students of Anambra State Polytechnic was correct and warranted more investigation. The practical implications and recommendations are discussed.